Microfoundations of innovation: A dynamic CEO capabilities perspective - Tim Heubeck; Reinhard Meckl (Managerial and Decision Economics, 2023)
Although sustainable competitive advantages in today's hypercompetitive economy call for strong management skills, the literature lacks a holistic understanding of the specific capabilities chief executive officers (CEOs) utilize to drive innovation. This article derives the dynamic CEO capabilities (DCCs) concept to examine whether CEOs' individual-level DCCs facilitate firm-level innovation and proposes that CEO power moderates this relationship. Results from a longitudinal sample of S&P 900 manufacturing firms confirm that strong DCCs drive innovation. Further, powerful CEOs can exert a more significant influence on firms' innovativeness through their DCCs, yet this effect is contingent on the type of CEO power.
Keywords: 650